2011
DOI: 10.1364/oe.19.020023
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale photonic crystal sensor arrays on monolithic substrates using side-coupled resonant cavity arrays

Abstract: We present nanoscale photonic crystal sensor arrays (NPhCSAs) on monolithic substrates. The NPhCSAs can be used as an opto-fluidic architecture for performing highly parallel, label-free detection of biochemical interactions in aqueous environments. The architecture consists of arrays of lattice-shifted resonant cavities side-coupled to a single PhC waveguide. Each resonant cavity has slightly different cavity spacing and is shown to independently shift its resonant peak (a single and narrow drop) in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…The calculated Q factors of the three peaks are equal to 44360, 28710 and 25029 respectively. These values showed an improvement in respect to other reports [17][18][19]21]. …”
Section: Phc Biosensors Array Designsupporting
confidence: 54%
See 1 more Smart Citation
“…The calculated Q factors of the three peaks are equal to 44360, 28710 and 25029 respectively. These values showed an improvement in respect to other reports [17][18][19]21]. …”
Section: Phc Biosensors Array Designsupporting
confidence: 54%
“…Examples of such systems include that of Mandal et al [16] who have firstly proposed a nanoscale optofluidic sensor array based on 1D PhC silicon waveguide for label-free detection of biomolecular interactions in aqueous environments. Yang et al [17] who have demonstrated a nanoscale PhC sensor array on monolithic substrates using a sidecoupled resonant cavity. Olyaee et al [18] have also demonstrated a sensor array based on side coupled H1 cavities to PhC waveguide where sensitivity of 165.45nm/RIU was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…We show, through simulations and experiments, the existence of transverse electric (TE) mode waveguiding and bending modes. C 2016 Author(s Methods proposed for the continuous active tuning or reconfiguring of photonic crystal (PC) structures have included the use of thermal, 1 optofluidic, 2 and gaseous plasma 3 elements. To our knowledge, reconfigurability of a PC with microsecond response capabilities has not been demonstrated.…”
mentioning
confidence: 99%
“…The simulations were completed using the first order basis function solver with a convergence criteria for the maximum change in S parameters between adaptive passes set at 1 percent. The computed E-field maps of the crystal were generated for all configurations to better understand how the PC interacts with the incident EM waves (see Figs (2) and (3)). At frequencies near the center of the bandgap (5.12 GHz) the signal is strongly attenuated and has a decay length of approximately two lattice constants, as seen in Fig.…”
mentioning
confidence: 99%
“…Light can then be guided by Bragg reflection from the surrounding PC along one or more straight, curved or intersecting line defects generated, for example by omitting cells of the periodic structure, changing the refractive index or deforming the unit cell geometry (Augustin et al 2006;Yang et al 2011;Gan and Li 2012). In a similar fashion, surrounding a point defect with a PC creates a resonator (Eichenfield et al 2009;Vignolini et al 2008).…”
mentioning
confidence: 99%